Confession and cartography: religion and the mapping of Poland-Lithuania - Doll, A (2021)
The religious aspect of early modern cartography remains under-appreciated, and little-understood. It has been overlooked, above all, because of a tenacious assumption: that cartography was secularised by the Ptolemaic revolution. In recent years this assumption has been challenged, but our knowledge remains severely limited; this is particularly true with regard to the great religious changes of the period: the Reformation, Counter-Reformation, and confessionalisation – a gap which this thesis is intended to fill. It approaches this issue through the lens of a case study, the cartography of the Polish-Lithuanian Commonwealth, from the later-16th to the early-18th century, and is guided by the question: ‘how did cartography respond to the religious changes within early modern Europe?’. In five chapters, it approaches this question from different angles: (1) the changing border of Europe (and continuing fear of paganism), (2) the idealised purification of Christendom in Georg Braun’s Civitates Orbis Terrarum (1572-1617), (3) the struggle to map confessional diversity (approached through a deconstruction of the mapping of the bishop) (4) the response to confessionalisation in the cartography of the Deluge (1655-60), (5) the place of cartography within Counter-Reformation Marian devotion.